Progressive Status of Antenatal Care Visits in Bangladesh: A Comparison Study - Biswas, Biplab; Yesmin, Farzana; Husain, Md Maidul; Khatun, Kakoli; Kumar, Nishith; Hoque, Md Aminul (International Journal of Statistical Sciences, 2024)
Antenatal care (ANC) visits is a proven way to reduce the maternal as well as infant mortality and WHO recommended four or more ANC visits during pregnancy. This study aimed to observe the progressive status of antenatal care visits (ANC) by exploring the trend of 1+ANC, WHO recommended 4+ANC visits and determine the factors of ANC visits frequency over the periods 2004 to 2018. Data on ANC were taken from Bangladesh Demographic and Health Surveys. This research used descriptive statistics (mean, median and prevalence) to observe the changes (%) of ANC visits. ANOVA, Kruskal-Walis, chi-square (bivariate analysis) test and mixed hurdle negative binomial regression were performed to identify the determinants of ANC visits frequency. The mean and prevalence (%) were increased for ANC over the periods however, 4+ANC visits was much lower than 1+ANC visits across the factors. Poorest rural women who living in Chittagong, Sylhet division had significant negative impacts on increasing the1+ANC visits frequency and are less likely to receive 4+ANC. On the other hand, wealthiest educated women with educated husband in Khulna, Rangpur region having more chances to get 4+ANC visits and positively effects on 1+ANC visits frequency for 2004 to 2018. Pregnancy wanted, Birth order number, and Last birth a C-Section are also the significant variable for 1+ and 4+ ANS. Although 1+ ANC visits have gradually increased in Bangladesh, the progress in achieving 4+ ANC visits has been much slower than expected. Therefore, the government and policymakers should focus their attention and prioritize interventions targeting the specific groups of women identified in this study. International Journal of Statistical Sciences ISSN 1683-5603 Vol. 24(2), November, 2024, pp 55-71